Receptiveness of Mobile Banking by Malaysian Local Consumers in Sabah: An Empirical Investigation - Hanudin, A.; Rostinah, S.; Masmurniwati, M.; Baba, Ricardo (ARRAY Development, 2011)
The aim of this study is to investigate the factors that determine the local people of Sabah (also known as Sabahan) bank customers' intention to use mobile banking. This study extends the applicability of the Technology Acceptance Model (TAM) to mobile banking and includes 'perceived credibility', 'perceived enjoyment' and 'perceived selfefficacy', in addition to 'perceived usefulness' and 'perceived ease of use'. The results indicate that perceived credibility, perceived enjoyment and perceived self-efficacy are important determinants to predicting the intentions of Malaysia's customers' to use mobile banking. However, perceived usefulness and perceived ease of use are not that of importance in predicting the intentions of the local customers to use mobile banking. The study contains a sample of local people of Sabah, in Eastern-Malaysia, and a limited number of measures in the model. Nonetheless, it provides new insight into factors affecting mobile banking use among local people in Sabah, a Malaysia's state. The results also provide general guidelines to banking institutions to better planning of mobile banking services as their future gadget of banking channel.